Touchless Mechanism to Detect Rhodamine B Concentration in Distilled Water Using Fiber Bundle - Samian; A. H. Zaidan; Patricia; R. N. Afifah; M. Yasin (International Journal of Optics)
Detection of rhodamine B concentration in distilled water can be conducted without direct contact between the sensor probe and the sample using fiber bundle as a sensor probe and concave mirror as a sample container. The fiber bundle used is a concentric and a pair bundle probe. The working mechanism of the sensor is based on the displacement sensor and absorption of rhodamine B on laser light at a wavelength of 543 nm. The concentration of rhodamine B was detected through the valley and the peak voltage resulting from the displacement of the sensor probe to the sample surface. The best performance is shown by a sensor that uses a concentric bundle as a probe with a detection range of 0–20 ppm with a resolution of 0.6 ppm.